Impact of Resident Participation on Operative Time and Outcomes in Otologic Surgery - Muelleman, Thomas; Shew, Matthew; Muelleman, Robert J; Villwock, Mark; Sykes, Kevin J; Staecker, Hinrich; Lin, James (Otolaryngology-head and neck surgery, 2018)
Objectives To describe the impact of resident involvement in tympanoplasty on operative time and surgical complication rates. Study Design Case series with chart review. Setting Tertiary medical center. Subjects and Methods Current Procedural Terminology codes were used to identify patients in the 2011-2014 public use files of the American College of Surgeons National Surgical Quality Improvement Program who underwent a tympanoplasty or tympanomastoidectomy. Cases were included if the database indicated whether the operating room was staffed with an attending alone or an attending with residents. Categorical and continuous variables were compared with chi-square, Fisher's exact, and Mann-Whitney U tests. Generalized linear models with a log-link and gamma distribution were used to examine the factors affecting operative time. Results Overall, 1045 cases met our study criteria (tympanoplasty, n = 797; tympanomastoidectomy, n = 248). Resident involvement increased mean operative time for tympanoplasties by 46% (107 vs 73 minutes, P < .001) and tympanomastoidectomies by 49% (175 vs 117 minutes, P < .001). While controlling for confounding factors, the variable with the largest impact on operative time was resident involvement. There were no significant differences observed in the rate of surgical complications between attending-alone and attending-resident cases. Conclusion Resident involvement in tympanoplasty and tympanomastoidectomy did not affect the surgical complication rate. Resident involvement increased operative time for tympanoplasties and tympanomastoidectomies; however, the specific reasons for the increase are not explained by the available data.